Enhanced ferroelectric switching characteristics of P(VDF-TrFE) for organic memory devices - Kusuma, Damar Yoga (2012)
In the following work, we report an approach to shorten the ferroelectric switching time of P(VDF-TrFE) film by blending with as-synthesized gold nanoparticles. Ferroelectric hysteresis measurements give remnant polarization and coercive field of 8 μC/cm2 and 50 MV/m, respectively. A series of electric pulses was applied for the characterization of ferroelectric polymers, and the switching time response was evaluated. More than 3 orders of magnitude reduction in switching time is observed for the polymer film blended with nanoparticles of the amount 1 × 10−6 wt %. The observed switching enhancements are discussed in terms of improved alignment of the ferroelectric crystal plane in the presence of the gold nanoparticles, whereby the aligned crystal planes experience a stronger effective field compared to the randomly oriented planes in pristine P(VDF-TrFE).